Solve for g 7(g-2)=5(g+4)

Math
7(g-2)=5(g+4)
Simplify 7(g-2).
Tap for more steps…
Apply the distributive property.
7g+7⋅-2=5(g+4)
Multiply 7 by -2.
7g-14=5(g+4)
7g-14=5(g+4)
Simplify 5(g+4).
Tap for more steps…
Apply the distributive property.
7g-14=5g+5⋅4
Multiply 5 by 4.
7g-14=5g+20
7g-14=5g+20
Move all terms containing g to the left side of the equation.
Tap for more steps…
Subtract 5g from both sides of the equation.
7g-14-5g=20
Subtract 5g from 7g.
2g-14=20
2g-14=20
Move all terms not containing g to the right side of the equation.
Tap for more steps…
Add 14 to both sides of the equation.
2g=20+14
Add 20 and 14.
2g=34
2g=34
Divide each term by 2 and simplify.
Tap for more steps…
Divide each term in 2g=34 by 2.
2g2=342
Cancel the common factor of 2.
Tap for more steps…
Cancel the common factor.
2g2=342
Divide g by 1.
g=342
g=342
Divide 34 by 2.
g=17
g=17
Solve for g 7(g-2)=5(g+4)

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top